2020
DOI: 10.21203/rs.3.rs-68757/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Home was not a Safe Haven: Women’s Experiences of Intimate Partner Violence during the COVID-19 Lockdown in Nigeria

Abstract: Background: Emergency situations, including epidemics, increase incidence of violence against women, especially intimate partner violence (IPV). This paper describes specific scenarios of IPV reported by women during the COVID-19 pandemic in Nigeria to provide insight for policy and programmatic efforts. Methods: This paper draws on seven de-identified case reports from organisations serving women experiencing IPV as well as media coverage of IPV cases in Nigeria, between April and May, 2020. Result: In most c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…34 A study finding from Nigeria showed that lockdowns for COVID-19 in their country have accidentally placed women at risk for experiencing more severe partner violence. 105 A study conducted in Taiwan revealed that anxiety, gender, age, perception of COVID-19 risk, and sexual orientation were factors associated with more changes in various aspects of the person's sex life. 97 The study suggested that COVID-19 and VAW are interrelated pandemics.…”
Section: Factors Associated With DV Against Women and Children During...mentioning
confidence: 99%
“…34 A study finding from Nigeria showed that lockdowns for COVID-19 in their country have accidentally placed women at risk for experiencing more severe partner violence. 105 A study conducted in Taiwan revealed that anxiety, gender, age, perception of COVID-19 risk, and sexual orientation were factors associated with more changes in various aspects of the person's sex life. 97 The study suggested that COVID-19 and VAW are interrelated pandemics.…”
Section: Factors Associated With DV Against Women and Children During...mentioning
confidence: 99%